L’incidence du milieu d’études sur les possibilités de choix de femmes autochtones : typologie de parcours scolaires - Joncas, Jo-Anni; Pilote, Annie (Canadian Journal of Higher Education, 2019)
This paper aims to assess the impact of the study environment on the opportunities of Indigenous women to complete the school pathway desired. During individual interviews, we collected 19 stories of Indigenous women’s experiences at two Quebec universities, one with several initiatives for indigenous students and the other with few. Through a typological analysis, four types of school pathways are presented according to the impact of the study environment; the pathway with: 1) pre-existing opportunities; 2) opportunities highlighted by the study environment; 3) rebound opportunities; and 4) driven by external impulses. Inspired by the capability approach, the results highlight the importance of focusing not only on the services and measures available to these students, but also on their ability to use them to achieve the desired academic path. This requires considering the factors that enable them to make effective use of educational resources for the purpose they choose.